2019
DOI: 10.1088/1361-6501/aafec1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of BeiDou satellite-induced code bias variations on precise time and frequency transfer

Abstract: The Chinese BeiDou navigation satellite system (BDS) is an emerging global navigation satellite system similar to the global positioning system (GPS), which provides positioning, navigation and timing services. The typical character of BDS code bias variation has received greater attention in relation to positioning and navigation in comparison with its underlying mechanism and effects on BDS carrier-phase time and frequency transfer. This study developed a code bias variation correction model. The improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Moreover, Tu et al [17] proposed a model of precise time transfer based on the triple-frequency uncombined observations of the BeiDou navigation satellite system (BDS). Zhang et al [18] developed a satellite-induced code variations model. They indicated that satellite-induced code variations needed to be corrected to improve the acc uracy of the time transfer, especially for long-distance time links.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Tu et al [17] proposed a model of precise time transfer based on the triple-frequency uncombined observations of the BeiDou navigation satellite system (BDS). Zhang et al [18] developed a satellite-induced code variations model. They indicated that satellite-induced code variations needed to be corrected to improve the acc uracy of the time transfer, especially for long-distance time links.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6 shows the DF time transfer results for GPS, Galileo, and BDS3 overlapping frequency (L1/L5, E1/E5a, B1/B2a) observations at time link BRUX-PTBB (left) and BRUX-KIRU (right), respectively. One can note that the variation of the clock difference series for GPS, Galileo, and BDS3 agreed well both at the BRUX-PTBB (Left) and BRUX-KIRU (Right), although obvious biases exist among the different series, which mainly cause by the different hardware delays for different satellite systems and can be calibrated in the time transfer campaign [35]. Meanwhile, the different estimated coordinate values of station for different satellite systems partly lead to these biases [36,37].…”
Section: Df Time and Frequency Transfermentioning
confidence: 83%
“…With the completion of the BDS and Galileo navigation systems, PPP time transfer technology based on multi-GNSSs will be realized and applied for remote time comparisons in the future. To date, time transfer technology based on BDS-2 has been studied [25,26]. Because the BDS-2 satellites mainly cover the Asia-Pacific region, the number of visible satellites in Europe is not enough for PPP calculations.…”
Section: Bds-3 Time Transfer With the Ppp Methodsmentioning
confidence: 99%